Role of health literacy on lifestyle and glycemic control among women with diabetes during pregnancy: a cross-sectional study - Babazadeh, Towhid; Pourrazavi, Sara; Ardeshiri, Zahra; Nadi, Akbar; Chollou, Khalil Maleki (Frontiers in Public Health, 2024)
Background The present study aimed to explore the impact of health literacy on the lifestyle of women with diabetes during pregnancy. Methods A cross-sectional study assessed the influence of some demographic characteristics and health literacy dimensions in predicting lifestyle and glycemic control in a sample of 230 women with diabetes during pregnancy. The data collection included a demographic form, a health literacy scale, and a lifestyle questionnaire. The data were analyzed using a one-way ANOVA and Pearson’s correlation coefficient. The predictors were determined using a hierarchical linear regression analysis. Results The participants had an average age of 27.74 years (SD = 6.54) and an average HbA1c level of 6.93% (SD = 1.93). Approximately 51.0% of the variation in lifestyle can be explained by health literacy (HL) and demographic variables (p-value <0.05). In addition, approximately 15.0% of the variation in HbA1c can be explained by health literacy, lifestyle, and demographic variables (p-value <0.05). Findings According to our findings, decision-making was found to be the strongest predictor of lifestyle. This study provides valuable information for nurses and other healthcare providers to help empower pregnant women to increase their health literacy and improve their lifestyle.